INDONESIA’S OPPORTUNITY TO DEVELOP MARITIME POTENCY: UTILIZING CHAIRMANSHIP IN IORA 2015 - Septyanto Galan Prakoso; Aditya Very Cleverina (Journal of Applied Economics in Developing Countries, 2016)
Indonesia is one of country located near Indian Ocean, it means that Indonesia is a maritime nation. Hence, Indonesia is a very big potential maritme to develope its economy. The aim of this paper is to determine how Indonesia used its opportunity to develop its maritime potency by utilizing IORA chairmanship during 2015-2017. The emphasis of this paper was placed on the examination of the perspectives and experiences of Indonesia as the largest archipelagic country and biggest economic growth in IORA. Indonesia could play a role, helping to strengthen the IORA and turn it into a respected and matured regional forum. By actuating this condition, Indonesia has a chance to get two advantages: in the domestic level, a significant progress in maritime sector of economic development can be achieved. Meanwhile, at the international level, this condition can be taken as a shortcut to propose the idea of Indonesia’s vision to international community in order to boost Indonesia's bargaining position in the international maritime issues.Keywords: IORA, maritime